Antecedents That Influence Employee Performance in PT Lion Air with Organizational Culture as a Mediation Variable - Ferian Amri; Masydzulhak Djamil Mz (Universitas Negeri Gorontalo, 2023)
This study aims to determine and analyze the effect of motivation and career development on employee performance and the organizational culture of PT Lion Air employees. This quantitative research takes place in PT Lior Air with 100 empolyees as the research sampel. The data collected by online qustionare and the analysis technique using statistical method ed by SmartPLS 3.0. Development have positive impact on corporate culture. Motivation have positive impact on employee performance. Meanwhile, Career development have no impact employee performance. Also Organizational culture have no impact employee performance.